Costs and benefits of low-sulphur fuel standard for Baltic Sea shipping. (15th December 2016) - Antturi, Jim; Hänninen, Otto; Jalkanen, Jukka-Pekka; Johansson, Lasse; Prank, Marje; Sofiev, Mikhail; Ollikainen, Markku
Abstract: The maximum allowable fuel sulphur content for shipping in the Baltic Sea dropped from 1%S to 0.1%S in 1 January 2015. We provide a cost-benefit analysis of the sulphur reduction policy in the Baltic Sea Sulphur Emission Control Area (SECA). We calculated the abatement costs based on shipowners' optimal decision-making in choosing between low-sulphur fuel and a sulphur scrubber, and the benefits were modelled through a high-resolution impact pathway analysis, which took into account the formation and dispersion of the emissions, and considered the positive health impacts resulting from lowered ambient PM2.5 concentrations. Our basic result indicates that for the Baltic Sea only, the latest sulphur regulation is not cost-effective. The expected annual cost is roughly €465 M and benefit 2200 saved Disability Adjusted Life-Years (DALYs) or monetized €105 M. Based on our sensitivity analysis, the benefits yet have a potential to exceed the costs. The analysis neither takes into account the acidifying impact of sulphur nor the impact North Sea shipping has on the cost-benefit ratio. Lastly, a similar approach is found highly recommendable to study the implications of the upcoming Tier III NOx standard for shipping. Highlights: Cost-benefit analysis is used to examine the impacts of low-sulphur fuel standard. Reduction in PM2.5 concentration improve Disability Adjusted Life Years by 2200. The expected net benefits are negative but become positive for extreme cases. The impact of the standard on competitiveness of exporting firms remains small.